Perspectives by Incongruity: “Religion” and “Transnationalism” - Palmié, Stephan (2013)
Aside from discussing the three articles in this special issue of Nova Religio on Religion and the Transnational Imagination, these brief comments aim to make a critical plea for conceptual clarification when it comes to what exactly the relatively novel, and arguably under-theorized term “transnational” might possibly mean when yoked to the historically old, but arguably equally problematic category, “religion.” My main argument is, if for different (though ultimately not altogether unrelated) reasons, both terms—at least as currently operationalized in much of the anthropology of religion, and religious studies more generally—not only fail to capture the social realities reported in the essays in this special issue, but also unhelpfully shore up a set of ideologies about the supposedly “novel” nature of our “globalized” human condition, that we might better rethink.
Keywords: Ideology; Religion; Globalization; Transnationalism